2019
DOI: 10.1126/sciadv.aau7886
|View full text |Cite
|
Sign up to set email alerts
|

Boosting contact sliding and wear protection via atomic intermixing and tailoring of nanoscale interfaces

Abstract: Multiple mixed interfaces and a critical carbon thickness in sub-10-nm overcoats are essential for low wear and friction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(177 reference statements)
0
22
0
Order By: Relevance
“…According to our benchmarks (tables S3 and S4), despite having a lower thickness, the COF and wear rate of the Cr20 coating are substantially lower than those reported values at the macroscale by date. A lower thickness is beneficial in certain situations wherein large thickness of the coatings may hinder their applications or degrade their functionality ( 3 ). Such wear behavior can be explained by considering the phenomena associated with varying the Cr deposition power.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our benchmarks (tables S3 and S4), despite having a lower thickness, the COF and wear rate of the Cr20 coating are substantially lower than those reported values at the macroscale by date. A lower thickness is beneficial in certain situations wherein large thickness of the coatings may hinder their applications or degrade their functionality ( 3 ). Such wear behavior can be explained by considering the phenomena associated with varying the Cr deposition power.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio I(D)/I(D′) can be used to obtain valuable information in this regard (42,47). It has been reported that I(D)/I(D′) is ~13 for sp 3 defects, ~10 for sp 2 -related defects, and ~7 for void defects. I(D)/I(D′) was observed to be ~10, ~7, ~13, and ~21 for Cr40, Cr80, Cr120, and Cr150, respectively.…”
Section: Determination Of Chemical and Nanostructural Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanotechnology is the dominant technology in today's world because of the scope of tailoring of the functionalities by altering the size, shape or constitution of nanomaterials [1][2][3]. The optimization of nanoparticle synthesis, therefore, has attracted a lot of attention as it is the prime tool in controlling the morphology of synthesized nanoparticles [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%